'What is the risk to me from COVID-19?': Public involvement in providing mortality risk information for people with 'high-risk' conditions for COVID-19 (OurRisk.CoV). Issue 6 (2021) - Banerjee, Amitava; Pasea, Laura; Manohar, Sinduja; Lai, Alvina G; Hemingway, Eade; Sofer, Izaak; Katsoulis, Michail; Sood, Harpreet; Morris, Andrew; Cake, Caroline; Fitzpatrick, Natalie K; Williams, Bryan; et al.
No abstract available